2018
DOI: 10.1073/pnas.1803420115
|View full text |Cite
|
Sign up to set email alerts
|

Five-S-isotope evidence of two distinct mass-independent sulfur isotope effects and implications for the modern and Archean atmospheres

Abstract: SignificanceAnomalous sulfur isotopic compositions preserved in sedimentary rocks older than ∼2.5 billion years have been widely interpreted as the products of UV photolysis of sulfur dioxide in an anoxic atmosphere and used to track the history of primitive Earth and evolution of early life. In this study, we present strong observational evidence that there is an additional process that produces similar anomalous sulfur isotope signatures. This previously unknown origin not only offers a tool for quantifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
123
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 46 publications
(162 citation statements)
references
References 59 publications
21
123
10
Order By: Relevance
“…In this case,t he exit channels such as aerosol formation and deposition become important. Am ost recent study revealed complex radical chain reactions of hydrocarbon in the inner zone of combustion flame before exposure to oxygen or OH radical in ambient air, [184] and therefore sulfur recombination reactions probably also occur in the combustion flame before oxidizing to SO 2 or sulfate.B ased on the observational evidence of combustionassociated D 36 S, [176] symmetric effect of sulfur-bearing species experimentally determined by Bains-Sahota and Thiemens, [129] and new theoretical investigation by Babikov, [181] Lin et al [176] proposed that symmetry-relevant and radical driven recombination reactions in combustion (e.g., SH + S! Thepossible mass independent isotope effect in the formation of S 2 ,t he starting molecule in as eries of sulfur recombination reactions,i sf urther investigated by calculating energy transfer mechanism and scattering resonance property.…”
Section: Underappreciated Mass Independent Sulfur Isotope Effectsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this case,t he exit channels such as aerosol formation and deposition become important. Am ost recent study revealed complex radical chain reactions of hydrocarbon in the inner zone of combustion flame before exposure to oxygen or OH radical in ambient air, [184] and therefore sulfur recombination reactions probably also occur in the combustion flame before oxidizing to SO 2 or sulfate.B ased on the observational evidence of combustionassociated D 36 S, [176] symmetric effect of sulfur-bearing species experimentally determined by Bains-Sahota and Thiemens, [129] and new theoretical investigation by Babikov, [181] Lin et al [176] proposed that symmetry-relevant and radical driven recombination reactions in combustion (e.g., SH + S! Thepossible mass independent isotope effect in the formation of S 2 ,t he starting molecule in as eries of sulfur recombination reactions,i sf urther investigated by calculating energy transfer mechanism and scattering resonance property.…”
Section: Underappreciated Mass Independent Sulfur Isotope Effectsmentioning
confidence: 99%
“…The 35 S nuclide is ac osmogenic isotope predominately produced in the stratosphere via the spallation of argon by cosmic rays. [179] By measuring all five sulfur isotopes ( 32 S, 33 S, 34 S, 35 S, and 36 S) in the same sulfate aerosols, Lin et al [176] found that D 33 Sv alues correlated with concentrations of stratospherically-sourced 35 S, while D 36 Sanomalies Figure 7. [179] By measuring all five sulfur isotopes ( 32 S, 33 S, 34 S, 35 S, and 36 S) in the same sulfate aerosols, Lin et al [176] found that D 33 Sv alues correlated with concentrations of stratospherically-sourced 35 S, while D 36 Sanomalies Figure 7.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 3 more Smart Citations